Development of Fine Motor Skills in Early Childhood Through Islamic Art Activities: A Case Study at RA. Labschool IIQ Jakarta Kindergarten Group B - Zaida, Nur Aini; Febrianti, Dinda Safira (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to describe the role of teachers, strategies, and challenges in developing fine motor skills in early childhood through Islamic art activities. A qualitative approach with a case study method was employed. The research subjects included children aged 5–6 years in the TK B group at RA. Labschool IIQ Jakarta, class teachers, and parents. Data were collected through observation, interviews, and documentation. The findings reveal that Islamic art activities such as basic calligraphy, coloring Islamic motifs, and hijaiyah letter collages effectively stimulate hand-eye coordination and fine motor skills. The strategies applied by teachers involved the use of engaging materials, thematic approaches based on Islamic values, and repetitive practice. The main challenges encountered included variations in children's skill levels and limited instructional time. This study recommends integrating Islamic art activities into early childhood education as a holistic medium that fosters both fine motor development and the internalization of spiritual values from an early age.